Dramaturgical possibilities within virtual realities: notes from AΦE's VR-performance Whist. Issue 2 (3rd July 2018) - Fromell, Amanda
ABSTRACT: This artistic position paper describes some of the dramaturgical possibilities that emerged from working as a dramaturg on AΦE's VR-performance, Whist . Specifically, it details three dramaturgical devices, which are distinctive to VR performance practices. It also points out current difficulties inherent within VR performances and discusses ways in which these can be resolved.